2017
DOI: 10.9788/tp2017.2-11en
|View full text |Cite
|
Sign up to set email alerts
|

Description and Analysis of Psychological Intervention with Dancers by the Software IRAMUTEQ

Abstract: Dancers live daily with pain, but often they do not know how to deal adequately with it. Based on this concern, we developed a psychological intervention for dancers to cope with pain, applied to 14 Jazz dancers, aged between 12 to 17 years old (M = 14.63; SD = 1.42), who have been competing internationally. This study presents the use of a software for analysis of the verbal reports of dancers and the mediator presented along the psychological intervention. Using the IRAMUTEQ software, we did the held monothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The software uses the Reinert method, 29 a factorial analysis where all the words are put together in a single cluster and divided according to chi-square criteria for the separation of words into classes. [29][30][31] Principal components analysis was applied to all the Likerttype questionnaires to assess the dimensionality and associated items to each component. Dimensionality was assessed using a scree plot, and the number of components that needed to be retained in each Likert-type questionnaire was assessed according to the 'elbow rule'.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…The software uses the Reinert method, 29 a factorial analysis where all the words are put together in a single cluster and divided according to chi-square criteria for the separation of words into classes. [29][30][31] Principal components analysis was applied to all the Likerttype questionnaires to assess the dimensionality and associated items to each component. Dimensionality was assessed using a scree plot, and the number of components that needed to be retained in each Likert-type questionnaire was assessed according to the 'elbow rule'.…”
Section: Qualitative Analysismentioning
confidence: 99%
“…It allows analyzing the closeness and the relationship between terms (in our case, between the active forms in the Elementary Context Units-ECU). Examples of the use of similarity analysis in the research process can be found in many studies from various fields of science, e.g., [61,62]. The analysis process begins by calculating the degree of association between all active forms in pairs, and then sequentially reducing the number of associations until a linked tree without cycles is obtained.…”
mentioning
confidence: 99%